Connecting to motor recovery after stroke. Issue 2 (6th May 2020) - Fowler, Jill H; Kalaria, Raj N
Abstract : This scientific commentary refers to 'Structural brain networks and functional motor outcome after stroke –a prospective cohort study', by Schlemm et al. (https://doi.org/10.1093/braincomms/fcaa001 ) in Brain Communications and 'Brain responsivity provides an individual readout for motor recovery after stroke' by Tscherpel et al. (https://doi.org/10.1093/brain/awaa127 ) in Brain